Potential of Fruit Extract from Green-Stemmed Binahong (Anredera cordifolia) as a Natural Chromophore for Solar Cell Development - Damayanti, Ni Noman Triyani; Sanjaya, I Gusti Made (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
The increasing demand for clean and renewable energy has driven the exploration of alternative materials for solar cell development. In this context, natural chromophores derived from plants offer an eco-friendly and sustainable solution due to their availability, low toxicity, and diverse molecular structures. This study investigates the chromophoric potential of the green-stemmed binahong (Anredera cordifolia) fruit and evaluates natural compounds that can be efficient light-absorbing materials in solar energy applications. Extracts of the binahong fruit were analyzed using Liquid Chromatography–Mass Spectrometry (LC-MS), revealing 66 distinct molecular peaks. Each compound was subjected to quantum chemical simulations using Time-Dependent Density Functional Theory (TD-DFT) following initial geometry optimization through Density Functional Theory (DFT) calculations. The simulations were conducted using the ORCA software, with molecular input prepared via the ChemCompute and Avogadro platforms. Parameters such as HOMO–LUMO energy levels and bandgap values were determined for all detected compounds. From these, 17 compounds exhibited favorable electronic characteristics, including bandgap values ranging from 1.3 to 4.4 eV and well-delocalized frontier orbitals. Notably, betalain compounds such as betanin and indicaxanthin showed strong visible light absorption and low energy gaps, while flavonoids and phenolic acids offered structural stability and tunable electronic properties. This research presents a novel computational approach to screening plant-based chromophores from non-model species, integrating LC-MS and TD-DFT data to highlight their light-harvesting capabilities. In conclusion, green-stemmed binahong is shown to be a promising source of natural chromophores for use in environmentally friendly solar technologies. The selected chromophores, especially those with optimal electronic configurations, are expected to be applied in future organic photovoltaic materials or integrated into green chemistry education as part of renewable energy awareness.